Vinyl sulfone analogs of lysophosphatidylcholine irreversibly inhibit autotaxin and prevent angiogenesis in melanoma. Issue 17 (1st September 2015) - Murph, Mandi M.; Jiang, Guowei W.; Altman, Molly K.; Jia, Wei; Nguyen, Duy T.; Fambrough, Jada M.; Hardman, William J.; Nguyen, Ha T.; Tran, Sterling K.; Alshamrani, Ali A.; Madan, Damian; Zhang, Jianxing; et al.
Graphical abstract: Abstract: Autotaxin (ATX) is an enzyme discovered in the conditioned medium of cultured melanoma cells and identified as a protein that strongly stimulates motility. This unique ectonucleotide pyrophosphatase and phosphodiesterase facilitates the removal of a choline headgroup from lysophosphatidylcholine (LPC) to yield lysophosphatidic acid (LPA), which is a potent lipid stimulator of tumorigenesis. Thus, ATX has received renewed attention because it has a prominent role in malignant progression with significant translational potential. Specifically, we sought to develop active site-targeted irreversible inhibitors as anti-cancer agents. Herein we describe the synthesis and biological activity of an LPC-mimetic electrophilic affinity label that targets the active site of ATX, which has a critical threonine residue that acts as a nucleophile in the lysophospholipase D reaction to liberate choline. We synthesized a set of quaternary ammonium derivative-containing vinyl sulfone analogs of LPC that function as irreversible inhibitors of ATX and inactivate the enzyme. The analogs were tested in cell viability assays using multiple cancer cell lines. The IC50 values ranged from 6.74 to 0.39 μM, consistent with a K i of 3.50 μM for inhibition of ATX by the C16 H33 vinyl sulfone analog CVS-16 (10b ). A phenyl vinyl sulfone control compound, PVS-16, lacking the choline-like quaternary ammonium mimicking head group moiety, had little effect on cell viability and did not inhibit ATX. Most importantly, CVS-16 (10b ) significantly inhibited melanoma progression in an in vivo tumor model by preventing angiogenesis. Taken together, this suggests that CVS-16 (10b ) is a potent and irreversible ATX inhibitor with significant biological activity both in vitro and in vivo.